First insights into macromolecular components analyses of an insect meal using hyperspectral imaging - Silva, Flávia Matias Oliveira da (2025)
The non-invasive nutritional analysis of feed through images captured by hyperspectral cameras represents an innovative and promising approach in the field of biotechnology. With this technology, it is possible to capture images at multiple wavelengths and identify unique spectral patterns associated with different molecular components, such as total fat and moisture. The technique is particularly valuable in biological environments, enabling a more detailed and comprehensive analysis of the presence and distribution of nutrients. The objective of this work was to perform a nutritional pre-characterization of Hermetia illucens (Black Soldier Fly-BSF) larvae meal, using hyperspectral images in the range of 400–1000 nm, with a spectral resolution of 7 nm and a spatial sampling of 512 pixels, and correlate them to traditional chemical analysis methods. The results were also compared to wheat flour samples. The chemical results of BSF meal indicated 7.2% ± 0.05% (w/w) and 28.15% ± 0.15% (w/w) in moisture and total fat content, respectively. When compared to wheat flour, BSF meal contains less total fat and this difference was clearly identified in the spectra derived from the hyperspectral images, which underscores the efficiency and utility of multispectral cameras to conduct real-time and non-destructive analyses. Furthermore, this analysis can be extended to other components (e.g., protein content), increasing the potential of the technique for feed characterization.